2016
DOI: 10.15261/serdj.23.63
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Indium from LCD Waste by Solvent Extraction and the Supported Liquid Membrane with Strip Dispersion Using D<sub>2</sub>EHPA as the Extractant

Abstract: The feasibility to recover indium (In) from discarded liquid crystal display (LCDs) panels by solvent extraction (SX) and a hollow fiber supported liquid membrane with strip dispersion (SLM-SD) system was investigated in this study. Di-(2-ethylhexyl)phosphoric acid (D 2 EHPA) was used as the extractant and the mobile carrier in SX and SLM-SD. The effect of different parameters such as pH, concentration of D 2 EHPA and stripping agents has been investigated for indium extraction. The average amount of indium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In general, LCD panels are manually crushed to produce small pieces (3-5 cm) that are easily ground into powder by mills (Gabriel et al, 2018(Gabriel et al, , 2020Jowkar et al, 2018). The traditional method is ball milling, which has been studied by many researchers who have investigated different parameters such as temperature and grinding time (Dhiman & Gupta, 2020;Ferella et al, 2016;Gabriel et al, 2020;Jowkar et al, 2018;Silveira et al, 2015;Yen et al 2016). Silveira et al (2015) compared three mills and found that a porcelain ball mill was optimal for obtaining small particle sizes (average 150 µm) in 120 min with minimal material loss (0.18 wt%) compared to knife and hammer mills.…”
Section: Comminution Of Lcd Panels To Obtain Powder Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, LCD panels are manually crushed to produce small pieces (3-5 cm) that are easily ground into powder by mills (Gabriel et al, 2018(Gabriel et al, , 2020Jowkar et al, 2018). The traditional method is ball milling, which has been studied by many researchers who have investigated different parameters such as temperature and grinding time (Dhiman & Gupta, 2020;Ferella et al, 2016;Gabriel et al, 2020;Jowkar et al, 2018;Silveira et al, 2015;Yen et al 2016). Silveira et al (2015) compared three mills and found that a porcelain ball mill was optimal for obtaining small particle sizes (average 150 µm) in 120 min with minimal material loss (0.18 wt%) compared to knife and hammer mills.…”
Section: Comminution Of Lcd Panels To Obtain Powder Samplesmentioning
confidence: 99%
“…Ferella et al (2016) found that the rod mill was a good option to achieve a 52 wt% finest fraction (average 212 µm) with the highest indium concentration in 30 min. Yen et al (2016) found that planetary ball milling for 120 min at 300 rpm was required to achieve a particle size of about 96 µm, while Assefi et al (2018) found that the ring mill could grind LCDs to powder with a particle size of 10 µm within 1 min after grinding with a guillotine blade.…”
Section: Comminution Of Lcd Panels To Obtain Powder Samplesmentioning
confidence: 99%
“…Several studies of selective lithium recovery from various solutions including geothermal brines have been reported, including adsorption, ion exchange, electrochemical extraction, and solvent extraction (Han et al, 2014;Yen et al, 2016;Jang and Chung, 2019;Battistel et al, 2020;Warren, 2021). Many researchers applied the adsorption and the ion exchange methods to recover lithium ions from various solutions, and many of them showed significantly selective lithium recovery results (Braun et al, 2002;Kumar et al, 2017;Wang et al, 2017;Jang and Chung, 2018;Goc et al, 2021;Warren, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the recyclability of the solvent makes this method beneficial. Based on the advantages described above, the solvent extraction method is used extensively in industrial applications to recover valuable metal ions from solutions (Yen et al, 2016). Many researchers have used various solvents to extract specific metal ions from aqueous solutions (Sadakane et al, 1975;Umetani et al, 1987;Hano et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of indium from etching solution can be of great help for balancing the demand and supply of indium and as well for environmental pollution control [4 -6]. One of potential techniques for indium recovery is SLMSD [4,5,7]. To understand the mass transfer mechanism as well as to establish a suitable model to describe this process, important factors affecting SLMSD performance must be evaluated.…”
Section: Introductionmentioning
confidence: 99%